PERSEPSI MAHASISWA MANAJEMEN PENDIDIKAN ISLAM TERHADAP PEMBELAJARAN BAHASA ARAB DI UNIVERSITAS ISLAM NEGERI YOGYAKARTA - Tia Nurhaeni; Mahmud Arif (Raudhah - Proud To Be Professional, 2023)
Abstract: Perception is the process of understanding oneself, judging, responding and interpreting information or stimuli from the surrounding environment received through the senses. This research was conducted in the Islamic Education Management UIN Sunan Kalijaga Yogyakarta. This study aims to obtain data related to the perceptions of Islamic Education Management students at UIN Sunan Kalijaga towards learning Arabic and to find out the reasons for the differences in perceptions they have. The methods used in this study is descriptive qualitative. Where the research data is located forms of observation and questionnaires obtained from object of research in the field. The results of this study are It is expected to be used as evaluation material and consideration by lecturers supporting Arabic courses, especially the Islamic Education Management Program in teaching Arabic. Keywords: Perception, Teaching Arabic